Metagenomic approaches to determine soil microbial communities associated with Armillaria root disease - Lalande, Bradley, author; Abdo, Zaid, author; Hanna, John, author; Page-Dumroese, Deborah, author; Warwell, Marcus, author; Tirocker, Joanne, author; Kim, Mee-Sook, author; Klopfenstein, Ned B., author; Stewart, Jane, author (Colorado State University. Libraries, 2017)
Armillaria root disease causes extensive damage to tree roots throughout the world and lacks successful management practices. Soil metagenomics and metatransciptomics may unlock the ability to understand how soil microbial communities interact with root pathogens, which may inhibit or facilitate the pathogenicity of disease. A western white pine (Pinus monticola) seed provenance plantation located within the Priest River Experimental Forest in northern Idaho provides the ability to sample numerous Armiilaria species along with bulk density soil cores. The basis of the research is to identify how soil microbial communities differ between different Armillaria species. Sixty-three trees were chosen with preference to trees that were previously identified to be infected with either A. solidipes or A. altimontana, and split between healthy and dead trees. At each tree, we sampled DBH, tree health, bulk density soil cores, and sampled for rhizomorphs. Soil samples are used to extract DNA and RNA to identify microbial communities involved with Armillaria species. Each DNA sample was amplified at the ITS-2 and 16S rDNA region to determine what microbes were present at each tree. Rhizomorphs were isolated and amplified using the translation elongation factor-1α locus to identify Armillaria species present within sampled trees. The ITS-2 and 16S microbial communities will be analyzed to show how they differ between each Armillaria species, tree health status, seed provenance, and soil properties. If microbial communities differ between species and tree health, this may unlock a new means of management for root diseases in a forest setting.
160 - Bradley M. Lalande
Keywords: metagenomics; soil; Armillaria